2011
DOI: 10.1186/1743-422x-8-116
|View full text |Cite
|
Sign up to set email alerts
|

Recent pattern of Co-infection amongst HIV seropositive individuals in tertiary care hospital, kolkata

Abstract: BackgroundOpportunistic Infections (OIs) and co-infections are the major cause of deaths amongst HIV infected individuals and this mostly depends upon the risk factors, type of exposure and geographic region. The commonest types of infections reported are tuberculosis, chronic diarrhoea, oral candidiasis, herpes simplex virus-2, cytomegalovirus, hepatitis B virus and hepatitis C virus. Due to the scarcity of OIs data available from this region, we had designed a study to determine the frequency of different OI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
63
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 26 publications
11
63
1
Order By: Relevance
“…This study indicated that the sexually active age groups from 25-44 years 302 (78.4%) were predominant followed by 45-64(16.1%) with an average age of 35.89 years and standard deviation of nine years (SD= 35 +/-9.16).This is consistent with the findings of other study which is done in India, age group of 20 -40 years (93%), with the mean age of 30.27 ± 5.5 years [14].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study indicated that the sexually active age groups from 25-44 years 302 (78.4%) were predominant followed by 45-64(16.1%) with an average age of 35.89 years and standard deviation of nine years (SD= 35 +/-9.16).This is consistent with the findings of other study which is done in India, age group of 20 -40 years (93%), with the mean age of 30.27 ± 5.5 years [14].…”
Section: Discussionsupporting
confidence: 82%
“…According to a study done on the pattern of Co-infection amongst HIV seropositive individuals in the tertiary care hospital, Kolkata; TB can occur at any point in the course of HIV infection [14]. Whereas in this study, of the total tuberculosis cases 69.2% were occurred in WHO clinical stage III and of the total study subjects 62(16.1%) and 247(64.2%) were in WHO clinical stage II and III respectively.…”
Section: Discussionmentioning
confidence: 67%
“…Also, Utsumi et al [11] in Indonesia and Geretti et al [12] in China reported results consistent with our findings (15.3%, and 16.7%, respectively), using ELISA to detect HBsAg. [14] and Saha et al in India [15] reported similar results to those revealed by our study (13.4%, 14.5%, and 15.19%, respectively), while higher rates of coinfection were reported by Franzeck et al who detected HBsAg in 28% of HIV-positive patients in Tanzania [16]. This rate of coinfection could reach 90% according to Sud et al depending on the prevailing risk factors in a given population [17].…”
Section: Discussionsupporting
confidence: 78%
“…12 The present study was carried out in a tertiary care hospital located in a rural setup with most of the patients being from rural population and HIV seropositive patients were mostly of middle age (31-40) which correlated with earlier studies. 2,13,14 The male: female ratio was found to be 4:1 in our study. The male: female ratios from other study groups 13-15 also tended to be higher.…”
Section: Discussionmentioning
confidence: 58%